1999
DOI: 10.1177/107755879905600204
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Treatment for Colorectal Cancer Medicare Patients in Two Group/Staff Health Maintenance Organizations and the Fee-for-Service Setting

Abstract: The current study compares treatment use and long-term survival in colorectal cancer patients between Medicare beneficiaries enrolled in two large prepaid group/staff health maintenance organizations (HMOs) and the fee-for-service (FFS) setting. The study is based on 15,352 colorectal cancer cases diagnosed between 1985 and 1992 and followed through 1995. Survival differences between the HMO and FFS cases were assessed using Cox regression. Treatment differences were evaluated using logistic regression. HMO ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…[19][20][21][22]41 Studies reported by Retchin et al 20,21 and Merrill et al 41 were restricted to patients insured by Medicare, a group for which we also found no differences in outcomes. Studies reported by Francis et al 22 and by Vernon et al 19 were not population based and were restricted to patients residing in single metropolitan areas (Seattle and Houston, respectively) that may not be representative of other parts of the country.…”
Section: Discussionmentioning
confidence: 55%
“…[19][20][21][22]41 Studies reported by Retchin et al 20,21 and Merrill et al 41 were restricted to patients insured by Medicare, a group for which we also found no differences in outcomes. Studies reported by Francis et al 22 and by Vernon et al 19 were not population based and were restricted to patients residing in single metropolitan areas (Seattle and Houston, respectively) that may not be representative of other parts of the country.…”
Section: Discussionmentioning
confidence: 55%
“…34 Previous studies have indicated that Medicare beneficiaries enrolled in health maintenance organization plans have better survival than patients enrolled in fee-for-service plans. 38,39 However, in a study that was restricted to patients who were enrolled in both Medicaid and Medicare at the time of their colorectal cancer diagnosis, no racial difference in survival was observed. 40 Dignam et al reported no significant racial difference in cancer-specific survival among patients with colon cancer (HR, 1.08; 95% CI, 0.94-1.25) or rectal cancer (HR, 1.25; 95% CI, 0.94-1.66) who were enrolled in the National Surgical Adjuvant Breast and Bowel Project trials, in which treatment regimens are controlled more rigorously.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only a handful of studies have addressed racial disparities in survival for colon cancer by adequately incorporating both treatment and SES 31,33,35,37 in addition to factors like cancer stage, tumor grade, and comorbid conditions. Among this limited number of studies, [28][29][30][31][32][33][34][35][36][37][38][39] the findings have been inconsistent. One of the main reasons for these inconsistent findings may be that previous studies had relatively small numbers of study patients.…”
mentioning
confidence: 99%